2017
DOI: 10.3390/su9010155
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nitrogen and Phosphorus Removal by Woody Plants with Deep-Planting Technique for the Potential Environmental Management of Carcass Burial Sites

Abstract: Phytoremediation is a promising technology to remediate carcass burial sites where deep soil layers are contaminated with nitrogen (N), phosphorus (P) and other potential contaminants by leachate. The current study was conducted to examine the remedial efficiency of two different woody plants, poplar (Populus euramericana) and willow (Salix alba), by employing the deep-planting technique for the enhanced removal of N and P for the soil affected by leachate. For this, pot trials to assess N and P removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A great number of current technologies have been developed to clean up the contaminated soil by Cd [34][35][36]. However, several conventional technologies, such as physical and chemical treatment approaches, are more expensive, less eco-friendly and bring secondary pollution problems [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…A great number of current technologies have been developed to clean up the contaminated soil by Cd [34][35][36]. However, several conventional technologies, such as physical and chemical treatment approaches, are more expensive, less eco-friendly and bring secondary pollution problems [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The fast growth and the apparent ability to rapidly uptake Cd may facilitate effective phytoaccumulation in a relatively short period, enabling the plants to be removed before setting seed and spreading. Though it is preferable for hyperaccumulators to have deep roots (e.g., poplar and willow), the shallow roots of I. glandulifera make it feasible to easily harvest the entire plant-something that is not typically possible-enabling the recovery of all the accumulated Cd [6,70,79].…”
Section: Discussionmentioning
confidence: 99%
“…Many plants that can be used as nitrogen and phosphate phytoremediator agents have been identified, including Ojoawo reported that Canna x generalis can effectively reduce nitrogen and phosphorus pollution by up to 51.2% 9 . Seo used Populus euramericana and Salix alba as phytoremediator agents and demonstrated effective performance in reducing nitrogen and phosphate pollution 10 and Malik used 3 plants namely Zantedeschia aethiopica, Pontederia lanceolata, Echinodorus palaefolius for heavy metal remediation in the textile industry wastewater 11 .…”
Section: Surakusumah Et Al | the Ability And Potential Of Echinodorus...mentioning
confidence: 99%